2009
DOI: 10.1016/j.stem.2009.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Reconstruction of Mouse Spermatogonial Stem Cell Self-Renewal In Vitro by Ras-Cyclin D2 Activation

Abstract: Spermatogonial stem cells (SSCs) undergo self-renewal division and support spermatogenesis. Although several cytokines coordinate to drive SSC self-renewal, little is known about the mechanisms underlying this process. We investigated the molecular mechanism by reconstructing SSC self-renewal in vitro without exogenous cytokines. Activation of Ras or overexpression of cyclins D2 and E1, both of which were induced by Ras, enabled long-term self-renewal of cultured spermatogonia. SSCs with activated Ras responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 36 publications
7
128
0
Order By: Relevance
“…However, the regulation of SSC pool size has not been fully elucidated. It has been observed that the overexpression of GDNF in transgenic mice leads to the development of malignant testicular cancer, similar to the situation with classic human seminoma, and the Ras-cyclin D2 activation induces the tumorigenesis of SSCs [35,36]. Moreover, it is believed that human spermatocytic seminoma may originate from SSCs [37].…”
Section: Discussionmentioning
confidence: 98%
“…However, the regulation of SSC pool size has not been fully elucidated. It has been observed that the overexpression of GDNF in transgenic mice leads to the development of malignant testicular cancer, similar to the situation with classic human seminoma, and the Ras-cyclin D2 activation induces the tumorigenesis of SSCs [35,36]. Moreover, it is believed that human spermatocytic seminoma may originate from SSCs [37].…”
Section: Discussionmentioning
confidence: 98%
“…The addition of GDNF and EGF and/or basic fibroblast growth factor (bFGF) induces SSC proliferation in vitro. Approximately 1-2% of the GS cells have SSC activity (4). GS cells from WT mice were infected with lentivirus vectors expressing candidate genes and Venus fluorescent marker gene under the control of an elongation factor2 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Although HRAS mutations are predicted to be enriched by selfish selection and have been implicated in SSC growth regulation (22), no study has attempted to document their occurrence directly in the sperm of healthy males. To explore further the link between selfish selection and human disease, we quantified the levels in blood and sperm of spontaneous mutations around p.G12 of HRAS, the codon most frequently affected both by germline CS mutations and by somatically acquired oncogenic mutations.…”
Section: Significancementioning
confidence: 99%